2012
DOI: 10.3109/14992027.2012.745200
|View full text |Cite
|
Sign up to set email alerts
|

Balance appointment information leaflets: Employing performance-based user-testing to improve understanding

Abstract: Some balance appointment PILs contain information which is difficult to find and/or understand for some readers. PILs should be evaluated prior to use using performance-based methods, since poor information provision may lead to increased patient anxiety and appointment non-attendance, cancellation, or postponement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In addition, there is a combined need to evaluate whether the structure and the content of the leaflet meets the understanding level of participants. In addition, it may be worthwhile verifying the availability and readability of the information leaflet directly among consumers by using performance-based user testing [5052].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a combined need to evaluate whether the structure and the content of the leaflet meets the understanding level of participants. In addition, it may be worthwhile verifying the availability and readability of the information leaflet directly among consumers by using performance-based user testing [5052].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to individual interviews used by most “user testings” [ 19 24 , 30 ], the discursive focus group setting also allowed for controversial discussion amongst the participants, which helped reveal contrasting opinions and misunderstandings, e.g. a discussion in one focus group revealed that some test-readers presumed that all donated specimens were analysed by the biobank and, hence, they believed that participants could hope for diagnostic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…PILs are perceived as useful, but they can also generate adverse emotional reactions ( Herber et al, 2014 ; Afreh et al, 2017 ; Thomas et al, 2018 ). In addition, the PILs in the current market are considerably illegible ( Rajasundaram et al, 2006 ; Symonds et al, 2011 ; Brooke et al, 2013 ; Spinillo, 2014 ; Bennin and Rother, 2015 ; Clausen et al, 2016 ; Alaqeel and al Obaidi, 2017 ; Haller et al, 2019 ; Zidarič and Kreft, 2019 ), impractical to use ( Sukkari et al, 2012 ), and can generate emotional discomfort and confusion due to their format. Therefore, several factors that facilitate the PIL understanding need to be consolidated in a future proposal to improve the PILs.…”
Section: Discussionmentioning
confidence: 99%
“…The leaflets must be clear and concise in their explanations and must be available in the user's language and adapted to their understanding (Clausen et al, 2016;Khodambashi et al, 2017). However, a considerable proportion of the leaflets evaluated in these articles did not meet these characteristics as they were not understood by the general public (Rajasundaram et al, 2006;Symonds et al, 2011;Brooke et al, 2013;Spinillo, 2014;Bennin and Rother, 2015;Alaqeel and al Obaidi, 2017;Haller et al, 2019), nor did they meet the parameters of utility (Sukkari et al, 2012), readability (Kasesnik and Kline, 2011), adaptation to the educational level of the target population (Cronin et al, 2011), or use of non-medical terminology (Hirsh et al, 2009;Bennin and Rother, 2015). Participants in other studies confirmed that the leaflets were clear, legible (Gustafsson et al, 2005;Williamson and Martin, 2010;Potter et al, 2014), and useful (Edwards et al, 2013), even though the participants showed low scores in a test on knowledge acquired from the PILs (Alaqeel and al Obaidi, 2017).…”
Section: Leaflet Variablesmentioning
confidence: 99%